Slovenščina v evropskem Babilonu - Stritar, Mojca (Jezik in slovstvo, 2011)
The article presents a description of the language situation of Slovene representatives in the European parliament 2004-2009. The results, which are based on interviews undertaken with representatives in 2007, show that although Slovene is one of the 23 official languages of the parliament, interpretation and translation are always provided primarily in symbolically important situations, while they are less frequent at working meetings. For representatives, therefore, a knowledge of foreign languages is essential, especially English, German and French. Despite this, all of the Slovene Euro-representatives support the existing multilingual arrangement.
Keywords: Slovene; slovenščina; raba jezikov; translation; prevajanje; interpretation; tolmačenje; uradni jeziki; znanje tujih jezikov; slovenski poslanci; Evropski parlament; 2004-2009